The Need Analysis of Teaching Material for Macroeconomic Theory Courses, Economic Education Study Program, Pamulang University - Hidayati, Syafaatul; Sholeh, Badrus; Anwar, Syamsul; Lukmana, Andri; Alfiansyah, Satria (Universitas Hamzanwadi, 2023)
The education system has various supporting components. One of them is teaching materials. Based on the results of observations made by observing students' learning behavior, it is known that many students are confused about choosing the right source. So far, lecturers have only used PPT learning resources. Thus, the aim of the research is to find out what teaching materials need to be developed for macroeconomic theory courses at the FKIP Pamulang University economics education study program according to student needs. The research method used is descriptive research with a survey method. Participants in the research were obtained using a non-probability sampling method, namely active students of the economics education study program FKIP UNPAM who were taking macroeconomic theory lectures, namely students taking semester 5, 27 students who participated in filling out a questionnaire via the Google Form link. The research data were analyzed descriptively qualitatively. research results regarding analysis of student needs for teaching materials in macroeconomic theory courses. It is hoped that future researchers will develop teaching materials that can meet student needs according to the learning objectives set and can overcome student difficulties in learning.